Temporal dynamics of wheat blast caused by Pyricularia oryzae Triticum lineage throughout the successive wheat cycles - Dorigan, Adriano Francis; Pozza, Edson Ampélio; Pereira, Renata Cristina Martins; Moreira, Silvino Intra; Ceresini, Paulo Cezar [UNESP]; Silva, Humberson Rocha; Alves, Eduardo (My University, 2024)
Wheat blast, caused by Pyricularia oryzae Triticum lineage (PoTl), can infect wheat leaves and heads. More information is needed on the pathogen biology and disease epidemiology of the isolate PoTl for the integrated management of wheat blast in Brazilian wheat fields. This study aimed to characterize the incubation period, latent period, and the temporal progress of wheat blast and to fit nonlinear models, describing the nature of an epidemic of the PoTl isolate 12.1.146 compared with the PoTl isolate Py6038, throughout five successive infection cycles of PoTl on wheat leaves and heads. Wheat blast occurred in all infection cycles. The incubation period and latent period of the PoTl isolate 12.1.146 were significantly shorter than that of the PoTl isolate Py6038. The secondary inocula produced by the PoTl isolate on symptomatic wheat leaves caused blast symptoms when inoculated on wheat heads. The area under the disease progress curve (AUDPC) was calculated based on disease severity. In all infection cycles, the AUDPC of the PoTl isolate 12.1.146 was significantly higher than that of the PoTl isolate Py6038. Between the 1st and 5th infection cycle, a significant reduction was observed in the AUDPC of the PoTl isolates. The nonlinear logistic model describe the disease progress curves (DPCs) of PoTl isolates on wheat leaves and heads best. Our findings indicate that the PoTl isolates did not maintain the same temporal dynamics after five successive infection cycles. These findings may have implications for the integrated management of the wheat blast pathogen in Brazilian fields.
Keywords: Disease control; Disease progress curve; Ecology and epidemiology; Nonlinear model; Pest management; Wheat blast